Aflatoxin B1-Induced Reproductive Toxicity in Male Rats: Possible Mechanism of Action. (May 2014) - Supriya, Ch.; Girish, B. P.; Reddy, P. Sreenivasula
Aflatoxin B1 (AFB1), one of the most common mycotoxins found in human foods, is principally hepatotoxic; however, it also affects reproduction. The aim of the present study was to elucidate the reproductive toxic effects and possible mechanism of action of AFB1 in rats. Male Wistar rats were injected intramuscularly with doses of 10, 20, or 50 µg AFB1/kg body weight on alternate days from 45 to 100 days of age. Significant reductions in body weights, relative weights of reproductive organs, daily sperm production, epididymal sperm count, viable sperm, motile sperm, and hypoosmotic swelling-tail coiled sperm were observed. Significant decreases in testicular steroidogenic enzymes and serum testosterone levels were also observed indicating decreased steroidogenesis. In silico docking studies illustrated AFB1 binds with steroidogenic acute regulatory (StAR) protein thereby affecting the transport of cholesterol into mitochondria resulting in decreased steroidogenesis.